Effect of Nitrogen Concentration on the Alkalophilic Microalga Nitzschia sp. NW129-a Promising Feedstock for the Integrated Production of Lipids and Fucoxanthin in Biorefinery - Cao, Zihao; Shen, Xiaotong; Wang, Xujing; Zhu, Baohua; Pan, Kehou; Li, Yun (Frontiers in Marine Science, 2022)
Microalgae are considered promising resources for producing a variety of high-value-added products, especially for lipids and pigments. Alkalophilic microalgae have more advantages than other microalgae when cultured outdoors on a large scale. The present study investigated the comprehensive effects of different nitrogen concentrations on fucoxanthin (Fx), lipids accumulation and the fatty acid profile of the alkaliphilic microalgae Nitzschia sp. NW129 to evaluate the potential for simultaneous production of Fx and biofuels. Fx and Lipids amassed in a coordinated growth-dependent manner in response to various concentrations, reaching 18.18 mg g-1 and 40.67% dry weight (DW), respectively. The biomass of Nitzschia sp. NW129 was 0.58 ± 0.02 g L-1 in the medium at the concentration of 117.65 mM. The highest productivities of Fx (1.44 mg L-1 d-1) and lipid (19.95 ± 1.29 mg L-1 d-1) were obtained concurrently at this concentration. Furthermore, the fatty acid methyl esters revealed excellent biofuel properties with an appropriate value of the degree unsaturation (49.97), cetane number (62.72) and cold filter plugging point (2.37), which met the European standards for biofuel production (EN14214). These results provided a reliable strategy for further industrialization and comprehensive production of biofuel and Fx by using the alkaliphilic microalgal Nitzschia sp. NW129.